First-principles calculations to investigate structural phase transformation to semi-conductor–metal transition and their impact on optical properties in lead titanium oxynitrate. Issue 14 (22nd September 2022) - Gillani, S. S. A.; Ahmed, Iqra; Zeba, I.; Shakil, M.; Ahmad, Riaz
ABSTRACT: Based upon the density functional theory with generalised gradient approximation and ultra-soft pseudo-potential, first-principles calculations investigate the structural, electronic, and optical properties of nitrogen-doped PbTiO3 . The computed results show that after nitrogen doping, the structure of PbTiO3 changes from cubic to pseudo-cubic tetragonal. Furthermore in an electronic perspective, we observe a significant reduction in the band gap (1.66 eV–0.56 eV) upon dopant incorporation and the band gap shifts from indirect to direct. For a detailed analysis of doping effects, the density of states, the partial density of states and elemental partial density of states are computed for pure and nitrogen-doped PbTiO3, which exhibit the strong coupling of O-2 p -states with Ti-3 d -states. Moreover, optical properties, such as the real and imaginary parts of the dielectric function, refractive index, reflection, absorption, energy loss function, and extinction coefficient for pure and doped lead titanate, have also been evaluated. The shifting of absorption edge towards lower energy values makes the nitrogen-doped lead titanate an attractive option for in optoelectronic frameworks.